Reorientasi Pendidikan Karakter dalam Menyongsong Indonesia Emas 2045: Sebuah Tinjauan dalam Perspektif Pedagogik Kritis - Nati Saripah; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
In achieving the goal of Golden Indonesia 2045, not only is economic progress the main focus, but also the development of strong and integrity-filled character. The foundation of character education for Indonesia's golden generation is a desire in the shift towards successful education in Indonesia. The aim of this research is to review from a critical pedagogical perspective the importance of reorienting character education towards Golden Indonesia 2045. The research method used is a literature study, which is a research technique based on collecting data from literature relevant to the research topic, then analyzing and interpreting it to gain a better understanding of the topic. The results of the discussion from this research are the challenges of character decadence faced by the Indonesian nation in achieving Golden Indonesia 2045, the correlation between Golden Indonesia 2045 and critical pedagogy, and the envisioned future Indonesian human. By strengthening character values through a critical and inclusive approach, it is hoped that the future generation will become agents of change who positively contribute to the nation's progress and realize the vision of Indonesia as a developed and civilized country by 2045.